Mengulik Kebijakan National Cycle Network di Inggris dan Harapan Bagi Indonesia - Shofiatul Ummah (Madani Jurnal Politik dan Sosial Kemasyarakatan, 2019)
The National Cycle Network is a policy of the British government that has succeeded in implementing national policies for its citizens by requiring all citizens to cycle nationally and be carried out seriously for more than 25 years to date. Indonesia has been building cycling paths since 2009, but many of its infrastructure is abandoned and neglected. The population that always increases every year, is not accompanied by the availability of vacant land and green open space, in addition to the number of population congestion also accompanied by the increase in vehicles will have a serious impact on the destruction of Indonesia's natural environment. Based on the State Law No. 32 of 2009 concerning Environmental Protection and Management that a good and healthy environment is the right of every citizen. One way that is expected to be able to change the mode of transportation for Indonesia when it is by applying the National Cycle Network in the UK with young methods and methods is accepted in Indonesia. This paper will provide a possible solution to facilitate the adoption of NCN in the UK to be applied in Indonesia. First, by building a cycling track with an adequate and safe traffic system. Second, there are clear regulations. And third, a long-term and consistent development system.